Felony Collateral Sanctions Effects on Recidivism: A Literature Review - Whittle, Tanya N. (Criminal justice policy review, 2018)
Despite recent advances in prisoner reentry and felony collateral consequences literature, the literature on collateral sanctions—intended legal consequences of criminal conviction—remains underdeveloped and unorganized. This article aims to take stock of the collateral sanctions literature to determine what the field currently knows about adult felony collateral sanctions’ effects on criminal recidivism. The author conducted a literature review of publications related to the topic of collateral sanctions and recidivism between 1995 and 2014. From these findings, the author outlines the state of current collateral sanctions research, identifies existing gaps in the literature, and discusses future research’s needed directions and challenges. Collateral sanctions and their effects remain mostly “invisible” despite a growing body of literature indicating that, at least for some sanctions, recidivism may be an unintended consequence of intended collateral sanction policies.